Análisis espacial de moniliasis (Moniliophthora perniciosa) a su diseminación en plantaciones de cacao (Theobroma cacao L.) CCN – 51 - Carrera Peña, Domenica Maite (2022)
Precision agriculture facilitates crop management, generating estimation maps are the best option to graphically represent geostatistical data of a crop in a certain area in order to know the analysis and disease of a crop. The general objective of this research work was to analyze the spread of Moniliasis (Moniliophthora perniciosa) in cocoa (Theobroma cacao L.) CCN-51 plantations using the spatial analysis technique. The present investigation was carried out on the La Mariscal farm in the agricultural area, located in the El Carmen Canton - Manabí Province, whose geographical coordinates are: 79°33'31.2" West longitude and 0°32'19.5" South latitude. Geostatistics was used to verify normality in the distribution of the data through the Smart Map plugin.